MOTIF TIRTAYASA, KEPANDEAN AND KAWANGSAN ON BANTEN BATIK IN MATHEMATICAL THEORY - Setianti, Selda; Hanafiani, Lia Gatra; Devianti, Vina; Wahyuni, Sri; Kusuma, Jaka Wijaya; Khan, Faisal (International Journal of Multidisciplinary Research and Literature, 2022)
Ethnomathematics was first described by D'Ambrosio (1984), who claims to be all the phenomena that shape cultural identities such as language, dialect, beliefs, values, clothing, customs, and behaviours related to various mathematical concepts. It is done. Indonesia is a country rich in culture. One of them is Batik Banten which is a cultural heritage. On October 2, 2009, UNESCO designated Batik as a cultural heritage belonging to Indonesia. Uki Kurniawan founded the Banten Batik Industry and Training Center on December 26, 2004, and was inaugurated on February 8, 2005, by the Minister of Industry. The Banten batik centre now has more than 75 varieties and motifs of Banten batik. This study will examine the Tirtayasa, Kepandean, and Kawangsan motifs. The research method used is descriptive qualitative research with an ethnographic approach, describing philosophical values and studying mathematical concepts. The concepts contained are flat shapes, transformations, similarity and congruence, and number patterns